HUBUNGAN PENGETAHUAN DAN SIKAP TENTANG KEPUTIHAN SERTA TINGKAT STRES TERHADAP PERILAKU VULVA HYGIENE PADA SISWI SMA YAPEMRI DEPOK TAHUN 2015 - Nurul Khusnul Chotimah, (2016)
Adolescence is a period in which the many changes cause health problems and psychological problems. Fluor Albus becomes reproductive health problems that often arise in adolescence. Knowledge and a good attitude prevent the Fluor Albus. The incidence of Fluor Albus can also be prevented with good hygiene behaviors regarding reproductive organs. Psychological problems that occur in teenagers is stress, mostly caused the teenagers can not to think hard and well behaved. This study aims to determine relationships between knowledge and attitudes about Fluor Albus and the level of stress on behavior Vulva Hygiene at the Yapemri Senior High School Depok Year 2015. This type of research was an analytic study with cross sectional design. This research has conducted in Yapemri Senior High School Depok by the number of samples that met the inclusion criteris as many as 70 people. Samples selection done by Simple Random Sampling method. Retrieving data using a questionnaire, and then analyzed by Chi Square. The results showed that there was no correlation between knowledge of Fluor Albus with the behavior of Vulva Hygiene (p = 0.658) and there was no correlation between attitudes about Fluor Albus with the behavior of Vulva Hygiene (p = 0.1000) and there a relationship between stress levels with behaviors Vulva Hygiene (p = 0. 024). Suggested respondents can improve knowledge and attitude and can control the stress that occurs.